MANAJEMEN STRATEGIS DALAM KONSEPTUALISASI SMART MANUFACTURING: IMPLIKASI TERHADAP DAYA SAING PERUSAHAAN - Ahmad Yafi Rangkuti; Septika Asri; Jihad Maulana; Aisyah Karimah; Hadi Supratikta (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Technological developments in the era of the Fourth Industrial Revolution and the transition toward Industry 5.0 require companies to implement adaptive and innovative strategic management. Smart manufacturing emerges as an approach that integrates digital technologies, automation, and data analytics with business strategy and human resource management. This article aims to conduct a literature review by emphasizing the role of strategic management, knowledge management, and strategic human resource planning in strengthening corporate competitive advantage. An analytical review method is employed to examine the concepts of strategic management, types of business strategies relevant to the context of smart manufacturing, and their implications for company competitiveness. The analysis reveals that the integration of digital technologies, differentiation strategies, innovation, and human resource readiness can drive companies toward achieving sustainable competitive advantage. The article concludes with the development of a conceptual framework that links strategic management, smart manufacturing, and competitive advantage within the context of digital transformation.